COVID-19 vaccine hesitancy among the adult population in Bangladesh: A nationwide cross-sectional survey. - Mohammad Bellal Hossain; Md Zakiul Alam; Md Syful Islam; Shafayat Sultan; Md Mahir Faysal; Sharmin Rima; Md Anwer Hossain; Abdullah Al Mamun (PLoS ONE)
Introduction Studies related to the COVID-19 vaccine hesitancy are scanty in Bangladesh, despite the growing necessity of understanding the population behavior related to vaccination. Thus, the present study was conducted to assess the prevalence of the COVID-19 vaccine hesitancy and its associated factors in Bangladesh to fill the knowledge gap. Methods and materials This study adopted a cross-sectional design to collect data from 1497 respondents using online (Google forms) and face-to-face interviews from eight administrative divisions of Bangladesh between 1-7 February 2021. We employed descriptive statistics and multiple logistic regression analysis. Results The prevalence of vaccine hesitancy was 46.2%. The Muslims (aOR = 1.80, p ≤ 0.01) and the respondents living in the city corporation areas (aOR = 2.14, p ≤0.001) had more hesitancy. There was significant variation in vaccine hesitancy by administrative divisions (geographic regions). Compared to the Sylhet division, the participants from Khulna (aOR = 1.31, p ≤0.001) had higher hesitancy. The vaccine hesitancy tended to decrease with increasing knowledge about the vaccine (aOR = 0.88, p≤0.001) and the vaccination process (aOR = 0.91, p ≤ 0.01). On the other hand, hesitancy increased with the increased negative attitudes towards the vaccine (aOR = 1.17, p≤0.001) and conspiracy beliefs towards the COVID-19 vaccine (aOR = 1.04, p≤0.01). The perceived benefits of COVID-19 vaccination (aOR = 0.85, p≤0.001) were negatively associated with hesitancy, while perceived barriers (aOR = 1.16, p ≤0.001) were positively associated. The participants were more hesitant to accept the vaccine from a specific country of origin (India, USA, Europe). Conclusions Our findings warrant that a vigorous behavior change communication campaign should be designed and implemented to demystify negative public attitudes and conspiracy beliefs regarding the COVID-19 Vaccine in Bangladesh. The policymakers should also think about revisiting the policy of the online registration process to receive the COVID-19 vaccine, as online registration is a key structural barrier for many due to the persistent digital divide in the country. Finally, the government should consider the population's preference regarding vaccines' country of manufacture to reduce the COVID-19 vaccine hesitancy.